Eksplorasi Konsep Etnomatematika dalam Struktur Arsitektur Candi Arjuna di Banjarnegara - Hanifah Dwi Sulistiowati; Prabu Biyatmoko; Hasna Ainun Fauziyyah; Anggun Badu Kusuma (Griya Journal of Mathematics Education and Application, 2026)
This study aims to explore ethnomathematical concepts embedded in the architectural structure of Candi Arjuna in Banjarnegara Regency as one of the Hindu cultural heritage sites in Central Java. The research employed a qualitative approach using an ethnographic research design, focusing on revealing mathematical meanings within the context of local culture. Data were collected through direct observation of the research object, limited interviews with relevant parties, and visual documentation of the temple’s architectural elements. The data were then analyzed descriptively using qualitative analysis procedures, including data reduction, data presentation, and conclusion drawing. The findings indicate that the front façade of Candi Arjuna implicitly integrates various mathematical concepts, including rectangular and triangular plane figures, vertical symmetry, and tiered patterns in the stepped-pyramid structure. The regularity of forms, uniformity of dimensions, and balance in the building’s composition demonstrate the application of contextual and meaningful mathematical principles within the cultural practices of the society at that time. These findings confirm that the architecture of Candi Arjuna is not only of historical and aesthetic value but also holds potential as a contextual ethnomathematics-based resource for mathematics learning that is closely connected to students’ cultural environments.